IMPROVING THERMAL EFFICIENCY OF SUBSIDIZED HOUSES THROUGH WINDOW-TO-WALL RATIO DESIGN - Syukur, Abdul; Alifia Niza Salafy; Yenni Yosita br Barus (Built Environment Studies, 2025)
Subsidized housing in Indonesia is often built with limited consideration for thermal comfort, prompting many residents to rely on air conditioning, which increases energy consumption. One of the factors that influences indoor thermal conditions is the Window-to-Wall Ratio (WWR), which determines how much sunlight and airflow can enter the space. This study explores how different WWR values affect the thermal performance of two subsidized housing types in Godean, Sleman—Griya Moyudan Asri and Godean Jogja Hills. Using quantitative analysis and simulation methods, temperature data were compared across existing conditions and adjusted WWR values of 10%, 20%, and 30%. The findings reveal that an increased WWR tends to elevate indoor temperatures, particularly during periods of high solar intensity. On the other hand, WWR values between 10% and 20% provide more consistent indoor temperatures and improve energy efficiency by reducing dependence on mechanical cooling. These results highlight the potential of passive design strategies, including optimal window sizing, pivot hinges, and effective shading, to enhance thermal comfort in tropical climates.